Establishment Islamic Character For Vocational School Students PN Integrated Meangin Through Religious Activities - Diana Wulandari; Syahril Syahril; Rifma Rifma (Edumaspul: Jurnal Pendidikan, 2023)
Character education is essential. very important, not only in school, but also at home and elsewhere even in the community. This study aims to find out what character education can influence in the Merangin Integrated Vocational Students in their senior year in high school. This study employed a qualitative descriptive strategy. And the findings of this study indicate that the factors that influence student character are school, family, and the surrounding environment Schools have a significant part in molding students' personalities, but the role of the family is as critical, parental affection for their children will have an impact on the child's personality. The communal environment is also responsible for molding children's character development. This is a qualitative descriptive research method that employs a qualitative methodology. Through Islamic education, one can increase faith and piety to God Almighty and form noble morals and avoid unwanted actions. The results of this study indicate that SMK PN Merangin has made character education a school advantage by making its students have Islamic character, various religious activities have supported the realization of students who are religious, and have good morals. All shockorder at school have played a role in carrying out religious activities. However, in order for the Islamic character to be formed to be even stronger, all school members must make Islamic character a school culture.